Dynamics of mitochondrial membrane potential and DNA damage during cryopreservation of cattle and buffalo bull spermatozoa - ELANGO, KAMARAJ; KUMARESAN, ARUMUGAM; ASHOKAN, MANOKARAN; KARUTHADURAI, THIRUMALAISAMY; NAG, PRADEEP; BHASKAR, MULINTI; PRASAD, BAKTHAVATHSALAM ARUN; JEYAKUMAR, SAKTHIVEL; MANIMARAN, AYYASAMY; BHAT, VINOD; RAMESHA, KEREKOPPA (The Indian Journal of Animal Sciences, 2021)
Understanding the changes in the spermatozoa during cryopreservation is indispensable for tailoring and increasing the efficiency of cryopreservation process success. However, the dynamics of damage to sperm organelles during different stages of cryopreservation is underexplored. This study assessed the mitochondrial membrane potential (MMP) and DNA damage during different stages of cryopreservation, viz. immediately after ejaculation, after equilibration and after freezing and thawing in cattle and buffalo spermatozoa using flow cytometry. Proportion of spermatozoa with high MMP decreased significantly after equilibration (from 66.06±4.59 to 42.58±6.30 in Holstein bulls and from 60.32±5.51 to 39.98±7.58 in buffalo bulls). Sperm DNA integrity [DNA fragmentation index (DFI %)] in Holstein Friesian (HF) bulls did not differ significantly between fresh and equilibrated samples but a significantly higher % DFI was observed in frozen-thawed semen samples as compared to both fresh and equilibrated samples. In contrast, % DFI in buffalo spermatozoa did not differ among the three stages of cryopreservation. It was concluded that mitochondrial damages occur during equilibration while chromatin damages occur during freezing and thawing of cattle bull spermatozoa; whereas buffalo bull spermatozoa were lesser susceptible to DNA damage during cryopreservation as compared to cattle spermatozoa.